A lithium ion battery electrolyte and a lithium ion battery containing the same
By using azacyclic carboxylic acid ester compounds and epoxy compounds as additives in lithium-ion battery electrolytes, it has solved the problems of instability and gas generation of existing electrolytes, and improved the battery Low-temperature and high-temperature cycling performance improves the stability of the electrolyte.
Patent Information
- Application Number
- CN202311024965.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-15
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2043-08-15
AI Technical Summary
Common additives such as vinyl sulfate in existing lithium-ion battery electrolytes are unstable during storage and use, and are prone to react with other components, resulting in failure of the electrolyte performance and a large amount of gas is generated during the battery formation period, which is used to provide automated production belts. It is inconvenient to come, and it is easy to generate production gas during high temperature circulation and storage, affecting battery performance.
Azeheterocyclic carboxylic acid ester compounds are used as additives to participate in the formation of positive and negative electrode films through electrolyte composed of non-aqueous organic solvents and lithium salts, inhibit the precipitation of metal ions, reduce the impedance of the negative electrode solid interface film, and improve the battery Low temperature properties and combined with epoxy compounds to enhance the stability of positive and negative electrode film formation.
It significantly improves the low-temperature performance of lithium-ion batteries, reduces gas production during battery formation and shelving, improves the stability of the electrolyte, can be stored for a long time under normal temperature conditions, and improves the high-temperature circulation of the battery and Low temperature cycle performance.
Smart Images

Figure CN117039151B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of lithium ion batteries, and in particular relates to a lithium ion battery electrolyte and a lithium ion battery containing the same. Background Art
[0002] Lithium-ion batteries, with their natural advantages such as high specific capacity, high cycle performance and environmental friendliness, have become one of the necessary paths to achieve the dual carbon goals and are widely used in power batteries, energy storage, 3C and other fields.
[0003] As one of the four main materials of lithium-ion batteries, electrolyte is usually composed of non-aqueous organic solvents, lithium salts and additives. Conventional non-aqueous organic solvents have chain carbonates, chain carboxylates and cyclic carbonates due to the differences in the physical properties of the solvents themselves. They are used in combination according to the specific application scenarios. The lithium salt is lithium hexafluorophosphate or a composite lithium salt of lithium hexafluorophosphate and lithium difluorosulfonyl imide. The additive is a substance with a small amount of addition but a single or multifunctional function. It can form a solid interface film on the surface of the positive and negative electrodes, significantly improving the performance of the battery. For example, vinyl sulfate, which is widely used in the industry, can improve the low-temperature, room-temperature and high-temperature performance of the battery. However, the storage conditions of vinyl sulfate are relatively harsh. It needs to be stored at low temperatures. The storage time is short and it is easy to discolor. Due to its own instability, it is easy to react with other components in the electrolyte, thereby causing the electrolyte performance to fail. In addition, batteries using electrolytes containing vinyl sulfate are prone to produce a large amount of gas during formation, which causes certain inconveniences in the automated production of batteries. Sometimes even secondary exhaust is required, so its use has certain disadvantages.
[0004] In order to improve the mass energy density and volume energy density of the battery, such as in the 3C industry, the lithium cobalt oxide (LCO) of the positive electrode material has gradually increased from the initial 4.2V to the current 4.48 or even 4.52V, while the negative electrode material has been changed from the original natural graphite (AG) to silicon-carbon or silicon-oxygen-carbon materials. In high-voltage lithium cobalt oxide and silicon-carbon batteries, a large amount of fluoroethylene carbonate and nitriles are usually used. Fluorinated ethylene carbonate is prone to gasification during high-temperature circulation and storage. Excessive use of nitriles will cause the viscosity of the electrolyte to increase, the conductivity to decrease, and the voltage of the battery to decay when it is left at full charge.
[0005] Therefore, it is necessary to develop some new additives to partially replace or completely replace the above additives, so as to further improve the performance of the battery. Summary of the invention
[0006] The first object of the present invention is to provide a lithium ion battery electrolyte and a lithium ion battery containing the same, so that the nitrogen heterocyclic carboxylic acid ester compounds in the electrolyte participate in the film formation of the positive and negative electrodes, inhibit the precipitation of metal ions during the circulation of high voltage materials, reduce the impedance of the negative electrode solid interface film, and significantly improve the low temperature performance of the battery.
[0007] In order to achieve the above object, the technical solution adopted by the present invention is:
[0008] A lithium-ion battery electrolyte, comprising a non-aqueous organic solvent, an electrolyte lithium salt, and an additive, wherein the additive comprises one or more nitrogen heterocyclic carboxylic acid ester compounds having a structure of formula (I),
[0009]
[0010] In formula (I), X is one of C, N, and S atoms; R1 is one of alkenyl groups having 3 to 5 carbon atoms, cyano groups having 1 to 3 carbon atoms, and trimethylsilyl alkane substituents having 1 to 3 carbon atoms; R2, R3, and R4 are independently selected from one of H, halogen, and alkyl substituents having 1 to 3 carbon atoms.
[0011] Furthermore, in the nitrogen heterocyclic carboxylate compound having the structure of formula (I), X is one of C and N atoms, R1 is selected from one of cyano groups having 1 to 3 carbon atoms and trimethylsilyl alkane substituents having 1 to 3 carbon atoms, and R2, R3 and R4 are all H.
[0012] According to some preferred and specific embodiments, the nitrogen heterocyclic carboxylic acid ester compound having the structure of formula (I) can be prepared by reaction.
[0013] Furthermore, the preparation method of the nitrogen heterocyclic carboxylic acid ester compound having the structure of formula (I) is as follows: dissolving the nitrogen heterocyclic compound in dichloromethane, adding a cyano compound or a trimethylsilyl alkane compound dropwise under the action of a catalyst composed of aluminum oxide and zinc oxide, and controlling the reaction temperature to react to obtain the compound.
[0014] Still more preferably, the cyano compound is cyanomethylol, and further preferably, it is added in the form of a dichloromethane solution of cyanomethylol.
[0015] Still more preferably, the trimethylsilylalkane compound is further preferably added in the form of a dichloromethane solution of trimethylsilylmethanol.
[0016] Preferably, the temperature of the system when the cyano compound or the trimethylsilylalkane compound is added dropwise is controlled to be 10° C. or 5° C. or less.
[0017] Preferably, after the dropwise addition of the cyano compound or trimethylsilylalkane compound is completed, the reaction temperature is maintained unchanged for 0.5 h to 1 h, then the temperature is raised to 15° C. for 0.5 h to 1 h, then the temperature is further raised to 20° C. for 0.5 h to 1 h, and finally the temperature is raised to reflux for 1 h to 2 h to obtain the product.
[0018] Furthermore, the nitrogen heterocyclic carboxylic acid ester compound having the structure of formula (I) is selected from one or more of the following compounds:
[0019]
[0020] According to some specific and preferred embodiments, the preparation method of the compound 1 is as follows: under the protection of an inert gas, 0.1 mol of N,N'-carbonyldiimidazole is dissolved in dichloromethane, a catalyst composed of aluminum oxide and zinc oxide is added, the temperature is lowered to below 10°C, and a dichloromethane solution of trimethylsilylmethanol is slowly added dropwise. After the addition is completed, the reaction is maintained below 5°C for 0.5h, the temperature is raised to 15°C for 0.5h, the temperature is then raised to 20°C for 0.5h, and the temperature is finally raised to reflux for 1h for ester exchange reaction. After the reaction is completed, compound 1 is obtained after post-treatment.
[0021] According to some specific and preferred embodiments, the preparation method of the compound 2 is: under the protection of an inert gas, N,N'-carbonyldiimidazole is dissolved in dichloromethane, a catalyst composed of aluminum oxide and zinc oxide is added, the temperature is lowered to below 5°C, and then a dichloromethane solution of cyanomethyl alcohol is slowly added dropwise. After the addition is completed, the reaction is maintained below 5°C for 0.5h, the temperature is raised to 15°C for 0.5h, the temperature is then raised to 20°C for 0.5h, and finally the temperature is raised to reflux for 1h for ester exchange reaction. After the reaction is completed, the compound 2 is obtained by post-treatment.
[0022] According to some specific and preferred embodiments, the preparation method of the compound 3 is: under the protection of an inert gas, N,N'-carbonyldipyrrole is dissolved in dichloromethane, a catalyst composed of aluminum oxide and zinc oxide is added, the temperature is lowered to below 10°C, and then a dichloromethane solution of cyanomethyl alcohol is slowly added dropwise. After the addition is completed, the temperature is maintained below 10°C for 0.5h, the temperature is raised to 15°C for 0.5h, the temperature is then raised to 20°C for 0.5h, and finally the temperature is raised to reflux for 1h for ester exchange reaction. After the reaction is completed, the compound 3 is obtained by post-treatment.
[0023] Preferably, the mass percentage of the nitrogen heterocyclic carboxylic acid ester compound having the structure of formula (I) in the aqueous electrolyte of the lithium ion battery is 0.01% to 5%.
[0024] Furthermore, the mass percentage of the nitrogen heterocyclic carboxylic acid ester compound having the structure of formula (I) in the lithium ion battery aqueous electrolyte is 0.5% to 3%, for example, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, or any of the above numerical values.
[0025] Preferably, the additive includes one or more epoxy compounds having the structure of formula (II):
[0026]
[0027]
[0028] In formula (II), R 1 and R 2 Independently selected from alkanes of 1 to 3 carbon atoms and fluorinated alkanes of 1 to 3 carbon atoms.
[0029] Furthermore, the alkane of 1 to 3 carbon atoms may be a straight chain or branched chain alkane of 1 to 3 carbon atoms; the fluoroalkane of 1 to 3 carbon atoms may be a straight chain or branched chain fluoroalkane of 1 to 3 carbon atoms.
[0030] Furthermore, the R 1 and R 2 Independently selected from one of a linear alkane with 1 to 3 carbon atoms and a linear fluorinated alkane with 1 to 3 carbon atoms.
[0031] According to some specific and preferred embodiments, the epoxy compound having the structure of formula (II) is selected from one or two of the following compounds:
[0032]
[0033] Furthermore, the epoxy compound having the structure of formula (II) is selected from compound B.
[0034] Preferably, the mass percentage of the epoxy compound having the structure of formula (II) in the aqueous electrolyte of the lithium-ion battery is 0.1% to 5%, for example, 0.1%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, or any of the above values.
[0035] Furthermore, the mass percentage of the epoxy compound having the structure of formula (II) in the lithium ion battery aqueous electrolyte is 0.5% to 2%, for example, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2.0%, or within the range of any of the above values.
[0036] Furthermore, the mass percentage of the epoxy compound having the structure of formula (II) in the aqueous electrolyte of the lithium ion battery is 0.5% to 1%.
[0037] Preferably, the additive further comprises other additives, and the other additives are selected from one or more of fluoroethylene carbonate (FEC), succinonitrile (SN), adiponitrile (ADN), 1,3,6-hexanetrinitrile (HTCN), 1,2-bis(cyanoethoxy)ethane (DENE), 1,3-propane sultone (PS), 1,3-propylene sultone (PST), vinyl vinylene carbonate (VEC), vinyl sulfate (DTD), tris(trimethylsilyl)borate (TMSB), tris(trimethylsilyl)phosphate (TMSP), and lithium difluorooxalatoborate (LiDFOB).
[0038] Furthermore, the other additives are selected from one or more of FEC, SN, DTD, and LiDFOB.
[0039] Furthermore, the other additive is LiDFOB.
[0040] Preferably, the mass percentage of the other additives in the aqueous electrolyte of the lithium ion battery is 0.5% to 10%, for example, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5%, 10%, or within the range of any of the above values.
[0041] Furthermore, the mass percentage of the other additives in the lithium-ion battery aqueous electrolyte is 0.5% to 5%.
[0042] Furthermore, the mass percentage of the other additives in the lithium-ion battery aqueous electrolyte is 0.5% to 3.5%.
[0043] Preferably, the electrolyte lithium salt is selected from one or more of lithium perchlorate (LiClO4), lithium tetrafluoroborate (LiBF4), lithium difluorooxalatoborate (LiDFOB), lithium hexafluorophosphate (LiPF6), lithium carbonate (Li2CO3), lithium sulfate (Li2SO4), lithium sulfite (Li2SO3), lithium nitrate (LiNO3), lithium bis(trifluoromethylsulfonyl)imide (LiTFSi), lithium difluorophosphate (LiPO2F2), and lithium difluorobis(oxalatophosphate) (LiDFOP).
[0044] Furthermore, the electrolyte lithium salt is selected from one or more of LiBF4, LiDFOB, LiPF6, LiNO3, LiFSi, and LiPO2F2.
[0045] Preferably, the concentration of the electrolyte lithium salt in the lithium ion battery electrolyte is 0.8M to 1.3M, for example, 0.8M, 0.85M, 0.9M, 0.95M, 1M, 1.05M, 1.1M, 1.15M, 1.2M, 1.25M, 1.3M, or within the range of any of the above values.
[0046] Furthermore, the concentration of the electrolyte lithium salt in the lithium ion battery electrolyte is 1M to 1.1M.
[0047] Preferably, the non-aqueous organic solvent is selected from one or more of propylene carbonate (PC), ethylene carbonate (EC), dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), ethyl methyl carbonate (EMC), methyl propyl carbonate (MPC), methyl formate (MF), ethyl acetate (EA), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), methyl acrylate (MA), N-methylpyrrolidone (NMP), N-methylformamide (NMF), N-methylacetamide (NMA), acetonitrile (ACN), N,N-dimethylformamide (DMF), sulfolane (THT), dimethyl sulfoxide (DMSO), dimethyl sulfide (DMS), γ-butyrolactone (GBL), and tetrahydrofuran (THF).
[0048] Furthermore, the non-aqueous organic solvent is selected from one or more of EC, EMC, EP and PP.
[0049] Furthermore, the non-aqueous organic solvent is a mixture of EC, EMC, EP and PP.
[0050] Preferably, the volume ratio of the EC, EMC, EP and PP is (1-3): (3-5): 1: (2-4); more preferably (1.5-2.5): (3.5-4.5): 1: (2.5-3.5).
[0051] In a second aspect, the present invention provides a lithium-ion battery, comprising a positive electrode sheet, a separator, a negative electrode sheet, and the lithium-ion battery electrolyte described above.
[0052] Preferably, the active material of the positive electrode sheet is a lithium transition metal composite oxide.
[0053] Furthermore, the lithium transition metal composite oxide comprises one or more of lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, and any one or more of the foregoing lithium transition metal composite oxides with the addition of other transition metals or non-transition metals.
[0054] Preferably, the active material of the negative electrode sheet is selected from one or more of soft carbon, hard carbon, artificial graphite, natural graphite, silicon, silicon oxides, silicon-carbon composites, lithium titanate, and metals that can form alloys with lithium.
[0055] Due to the application of the above technical solution, the present invention has the following advantages compared with the prior art:
[0056] In the present invention, by adding nitrogen heterocyclic carboxylic acid ester compounds into the lithium ion battery electrolyte, the positive and negative electrode film formation can be participated in, the electrode kinetics and thermodynamics properties can be improved, the impedance of the interface film can be reduced, the low temperature performance of the battery can be improved, and the gas production during the battery formation and storage process can be reduced. At the same time, the battery can be stored for a long time at room temperature, thereby improving the stability of the electrolyte. DETAILED DESCRIPTION
[0057] All features disclosed in the present invention, or all steps in the methods or processes disclosed, except mutually exclusive features or steps, may be combined in any manner.
[0058] In view of the deficiencies in the prior art, the inventor of this case has proposed the technical solution of the present invention after long-term research and extensive practice. The technical solution, its implementation process and principle will be further explained as follows.
[0059] The nitrogen heterocyclic carboxylic acid ester compound having the structure of formula (I) is selected as the additive in the present invention, which can participate in the film formation of the positive and negative electrodes, improve the electrode kinetics and thermodynamic properties, reduce the impedance of the interface film, enhance the low temperature performance of the battery, reduce the gas production during the battery formation and storage process, and can be stored for a long time at room temperature, thereby improving the stability of the electrolyte.
[0060] Specifically, the presence of silicon-based groups in compound 1 can consume trace amounts of water in the battery and reduce the generation of HF, thereby avoiding HF damage to the solid interface film under cycling and storage conditions, which is beneficial to the improvement of high-temperature performance. However, the viscosity of the electrolyte increases due to the addition of silicon-based groups, which reduces the low-temperature performance of the battery. The cyano groups in compounds 2 and 3 can form complexes with cobalt metal ions in the material in high-voltage lithium cobalt oxide, reduce the dissolution of metal ions, reduce the catalytic decomposition of metal ions on the electrolyte, and improve the cycle performance of high-voltage batteries. The nitrogen content in the imidazole group and pyrrole group in compounds 2 and 3 is different. The increase in nitrogen content can reduce the film impedance after film formation on the one hand, and on the other hand, it can also increase the interaction between the compound and H + The ability of ion binding further reduces the generation of HF.
[0061] Furthermore, adding an epoxy compound having the structure of formula (II) to the electrolyte of a lithium-ion battery and combining it with a nitrogen heterocyclic carboxylic acid ester compound having the structure of formula (I) can further enhance the stability of the positive and negative electrode film formation and improve the cycle performance of the battery under high voltage conditions. In particular, the selection of compound A or compound B can improve the battery performance, but the improvement effect of compound B is more obvious. This is because under similar structural conditions, the asymmetry of the six-membered ring makes compound B more unstable, and it is easier to undergo a ring-opening reaction than compound A, and a polymer with a longer carbon chain is generated.
[0062] Furthermore, the conventional voltage range of cobalt oxide lithium batteries is 3.0-4.2V, and a greatly increased voltage upper limit means faster cycle decay. In this application, in the lithium-ion battery electrolyte, a nitrogen heterocyclic carboxylic acid ester compound having a structure of formula (I) and an epoxy compound having a structure of formula (II) are added as additives, and synergistically with other additives and lithium salts in the system, the upper limit of the operating voltage of the obtained lithium-ion battery can be increased to 4.45V, while having good high-temperature cycle performance and low-temperature cycle performance, avoiding the battery from decaying too quickly during the cycle at this operating voltage.
[0063] The present invention is further described below in conjunction with the examples. However, the present invention is not limited to the following examples. The implementation conditions used in the examples can be further adjusted according to the different requirements of specific use, and the implementation conditions not specified are conventional conditions in the industry. The technical features involved in each embodiment of the present invention can be combined with each other as long as they do not conflict with each other.
[0064] The experimental methods in the following examples are all conventional methods unless otherwise specified; the experimental materials used are all purchased from conventional biochemical reagent manufacturers unless otherwise specified.
[0065] It should be noted that, unless otherwise specified herein, “%” represents mass percentage.
[0066] Example 1
[0067] The present embodiment provides a lithium ion battery electrolyte, and the preparation method is as follows: in a glove box filled with argon, ethylene carbonate (EC), diethyl carbonate (EMC), ethyl propionate (EP), and propyl propionate (PP) are mixed in a volume ratio of EC:EMC:EP:PP=2:4:1:3 to obtain a mixed solution, and then 1.15 mol / L lithium hexafluorophosphate (LiPF6) is slowly added to the mixed solution, and then 0.5% of the total mass of the electrolyte is added. Compound 1 and 0.5% of the total mass of the electrolyte are added. Lithium difluorooxalatoborate (LiDFOB) are added, and the lithium ion battery electrolyte of Example 1 is obtained after stirring evenly.
[0068] This embodiment also provides a lithium-ion battery, wherein a positive electrode active material, lithium cobalt oxide (LiCoO2), a conductive agent, acetylene black, and a binder, polyvinylidene fluoride (PVDF), are fully stirred and mixed in an N-methylpyrrolidone solvent system in a mass ratio of 95.8:2.2:2, and then coated on an aluminum foil, dried, and cold pressed to obtain a positive electrode sheet.
[0069] The negative electrode active material artificial graphite, the conductive agent acetylene black, the binder styrene butadiene rubber (SBR), and the thickener sodium carboxymethyl cellulose (CMC) are fully stirred and mixed in a deionized water solvent system in a mass ratio of 96:2.5:0.5:1, and then coated on a copper foil, dried, and cold pressed to obtain a negative electrode sheet.
[0070] Polyethylene (PE) is used as a base film and a nano-aluminum oxide coating is coated on the base film as an isolation film.
[0071] The positive electrode sheet, the isolation film, and the negative electrode sheet are stacked in sequence and then wound in the same direction to obtain a bare cell, which is placed in an outer package, injected with the electrolyte prepared in each embodiment and comparative example, and subjected to packaging, 45° C. storage, high-temperature fixture formation, secondary packaging, capacity division and other processes to obtain a high-voltage lithium cobalt oxide lithium-ion battery.
[0072] The lithium ion batteries of Examples 2 to 16 and Comparative Example 1 are all prepared according to the preparation method in Example 1 above, with the difference that the types and amounts of additives and other additives in the lithium ion battery electrolyte are different. The specific composition ratios of the components of the electrolyte in each example and comparative example are shown in Table 1. The "%" in Table 1 refers to the percentage of the mass of the corresponding additive to the total mass of the electrolyte.
[0073] Table 1 Proportions of positive electrode materials and electrolytes in the batteries obtained in the examples and comparative examples
[0074]
[0075] Among them, the preparation method of compound 1 is: under the protection of inert gas, 0.1 mol N, N'-carbonyldiimidazole (CAS No.: 530-62-1) is dissolved in dichloromethane, 1.70g catalyst composed of aluminum oxide and zinc oxide (the mass ratio of aluminum oxide to zinc oxide is 1:1.5) is added, the temperature is lowered to below 10°C, and then 0.12 mol of trimethylsilylmethanol (CAS No.: 3219-63-4) in dichloromethane is slowly added dropwise. After the addition is completed, the reaction is maintained below 5°C for 0.5h, the temperature is raised to 15°C for 0.5h, the temperature is then raised to 20°C for 0.5h, and finally the temperature is raised to reflux for 1h for ester exchange reaction. After the reaction is completed, the compound 1 is obtained after post-treatment, and the structural formula is:
[0076] The preparation method of compound 2 is as follows: under the protection of inert gas, 0.1 mol N, N'-carbonyldiimidazole (CAS No.: 530-62-1) is dissolved in dichloromethane, 1.75 g of a catalyst composed of aluminum oxide and zinc oxide (the mass ratio of aluminum oxide to zinc oxide is 1:1.5) is added, the temperature is lowered to below 5°C, and then 0.13 mol of a dichloromethane solution of cyanomethyl alcohol is slowly added dropwise. After the addition is completed, the temperature is maintained below 5°C for 0.5 h, the temperature is raised to 15°C for 0.5 h, the temperature is then raised to 20°C for 0.5 h, and finally the temperature is raised to reflux for 1 h for transesterification. After the reaction is completed, the compound 2 is obtained after post-treatment, and the structural formula is:
[0077]
[0078] The preparation method of compound 3 is as follows: under the protection of inert gas, 0.1 mol N, N'-carbonyldipyrrole (CAS No. 54582-33-1) is dissolved in dichloromethane, 1.62 g of a catalyst composed of aluminum oxide and zinc oxide (the mass ratio of aluminum oxide to zinc oxide is 1:1.5) is added, the temperature is lowered to below 10°C, and then 1.1 mol of a dichloromethane solution of cyanomethyl alcohol is slowly added dropwise. After the addition is completed, the temperature is maintained below 10°C for 0.5 h, the temperature is raised to 15°C for 0.5 h, the temperature is then raised to 20°C for 0.5 h, and finally the temperature is raised to reflux for 1 h for transesterification. After the reaction is completed, the compound 3 is obtained after post-treatment, and the structural formula is:
[0079]
[0080] Performance Testing
[0081] The performance of the batteries prepared in Examples 1 to 16 and Comparative Example 1 was tested according to the following method.
[0082] (1) Normal temperature cycle performance test
[0083] Under the condition of 25℃, at 25℃, the divided battery is charged to 4.45V at 1C constant current and constant voltage, with a cut-off current of 0.02C, and then discharged to 3.0V at 1C constant current. After 800 cycles of charge and discharge, the 800th cycle capacity retention rate is calculated. The calculation formula is as follows:
[0084] The 800th cycle capacity retention rate (%) = (800th cycle discharge capacity / first cycle discharge capacity) × 100%,
[0085] (2) 60℃ constant temperature storage capacity remaining rate test
[0086] First, the battery was charged and discharged three times at 1C at room temperature (3.0-4.45V), and the discharge capacity C0 of the battery before storage was recorded. Then the battery was charged to 4.45V at constant current and constant voltage. The volume of the test battery was V0. Then the battery was placed in a 60℃ constant temperature box for 7 days. After the storage was completed, the battery was taken out. After the battery was cooled at room temperature for 24 hours, the volume of the battery was recorded again as V1. Then the battery was discharged to 3.0V at 1C at constant current. The discharge capacity C1 of the battery after storage was recorded. The remaining capacity of the battery after 7 days of constant temperature storage at 60℃ was calculated. The calculation formula is as follows:
[0087] After 7 days of storage at 60℃, the remaining capacity = C1 / C0×100%;
[0088] After 7 days of constant temperature storage at 60°C, the volume change rate = V1 / V0×100%.
[0089] (3) -10℃ Cyclic Performance Test
[0090] At -10℃, charge the divided battery to 4.45V at 1C constant current and constant voltage, with a cut-off current of 0.02C, and then discharge it to 3.0V at 1C constant current. Repeat this cycle. After 300 cycles of charge and discharge, calculate the 300th cycle capacity retention rate. The calculation formula is as follows:
[0091] The 300th cycle capacity retention rate (%) = (300th cycle discharge capacity / first cycle discharge capacity) × 100%.
[0092] The calculation results are shown in Table 2.
[0093] Table 2 Battery performance test results of the embodiments and comparative examples
[0094]
[0095] By comparing Examples 1-8 and Comparative Example 1, it can be seen that Compound 1, Compound 2 and Compound 3 as additives can improve the room temperature cycle performance, high temperature shelf performance and low temperature and high pressure cycle performance of the battery to a certain extent, among which Compound 1 has the most obvious effect on the battery, and the optimal dosage of Compound 1 is 1%.
[0096] The results of Examples 9 to 16 show that after the combination of Compound 1 and Compound B, the high-temperature shelf effect is further improved; after the combination of Compounds 2 and 3 and Compound B, the high-pressure cycle performance is further improved.
[0097] In summary, the compounds and combinations of compounds in the present invention have better performance than existing additives in some aspects, and thus can replace or partially replace existing additives.
[0098] The above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with the technology to understand the content of the present invention and implement it accordingly, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes made according to the spirit of the present invention.
Claims
1. A lithium ion battery electrolyte, comprising a non-aqueous organic solvent, an electrolyte lithium salt, and an additive, characterized in that: The additive comprises one or more nitrogen heterocyclic carboxylic acid ester compounds having the structure of formula (I), In formula (I), X is one of C, N, and S atoms; R1 is one of an alkenyl group having 3 to 5 carbon atoms, a cyano group having 1 to 3 carbon atoms, and a trimethylsilyl alkane substituent having 1 to 3 carbon atoms; R2, R3, and R4 are independently selected from one of H, halogen, and an alkyl substituent having 1 to 3 carbon atoms; The additive also includes one or more epoxy compounds having the structure of formula (II): In formula (II), R 1 and R 2 Independently selected from alkanes of 1 to 3 carbon atoms and fluorinated alkanes of 1 to 3 carbon atoms.
2. The lithium-ion battery electrolyte according to claim 1, characterized in that: In the nitrogen heterocyclic carboxylate compound having the structure of formula (I), X is one of C and N atoms, R1 is selected from one of cyano groups having 1 to 3 carbon atoms and trimethylsilyl alkane substituents having 1 to 3 carbon atoms, and R2, R3 and R4 are all H.
3. The lithium ion battery electrolyte according to claim 2, characterized in that: The nitrogen heterocyclic carboxylic acid ester compound having the structure of formula (I) is selected from one or more of the following compounds:
4. The lithium ion battery electrolyte according to any one of claims 1 to 3, characterized in that: The mass percentage of the nitrogen heterocyclic carboxylic acid ester compound having the structure of formula (I) in the aqueous electrolyte of the lithium ion battery is 0.01% to 5%.
5. The lithium-ion battery electrolyte according to claim 1, characterized in that: The epoxy compound having the structure of formula (II) is selected from one or two of the following compounds: And / or, the mass percentage of the epoxy compound having the structure of formula (II) in the aqueous electrolyte of the lithium ion battery is 0.1% to 5%.
6. The lithium ion battery electrolyte according to claim 1, characterized in that: The additives also include other additives, which are selected from one or more of fluoroethylene carbonate, succinonitrile, adiponitrile, 1,3,6-hexanetrinitrile, 1,2-bis(cyanoethoxy)ethane, 1,3-propane sultone, 1,3-propylene sultone, vinyl vinyl carbonate, vinyl sulfate, tris(trimethylsilyl)borate, and tris(trimethylsilyl)phosphate.
7. The lithium ion battery electrolyte according to claim 6, characterized in that: The mass percentage of the other additives in the lithium ion battery water electrolyte is 0.5% to 10%.
8. The lithium-ion battery electrolyte according to claim 1, characterized in that: The electrolyte lithium salt is selected from one or more of lithium perchlorate, lithium tetrafluoroborate, lithium difluorooxalatoborate, lithium hexafluorophosphate, lithium carbonate, lithium sulfate, lithium sulfite, lithium nitrate, lithium bis(trifluoromethylsulfonyl)imide, lithium difluorophosphate, and lithium difluorobis(oxalatophosphate); And / or, the concentration of the electrolyte lithium salt in the lithium ion battery electrolyte is 0.8M to 1.3M; And / or, the non-aqueous organic solvent is selected from one or more of propylene carbonate, ethylene carbonate, dimethyl carbonate, diethyl carbonate, dipropyl carbonate, ethyl methyl carbonate, methyl propyl carbonate, methyl formate, ethyl acetate, methyl butyrate, methyl acrylate, N-methylpyrrolidone, N-methylformamide, N-methylacetamide, acetonitrile, N,N-dimethylformamide, cyclopentane, dimethyl sulfoxide, methyl sulfide, γ-butyrolactone, and tetrahydrofuran.
9. A lithium ion battery, characterized in that: The invention comprises a positive electrode sheet, a separator, a negative electrode sheet and the lithium-ion battery electrolyte according to any one of claims 1 to 8.
